CAPABILITY OF ISOLATED BACTERIA FROM SOIL AT DAIRY FARM INDUSTRY IN REDUCING AMMONIA - Fitriyanto, Nanung Agus; Wahyuningsih, Rina (2014)
Odor are usually generated by animal from the dairy farm industry possibly cause environmental problems such as ammonia emission in high level which can reduce productivity of dairy cows and endanger the health of person who living inside the cage or community who living nearby the dairy cows industries. Transformation of volatile ammonia to non-volatile species is a major biological treatment process comprising of coupled nitrification and denitrification processes. The aim of this research was to isolate bacteria which have ability in reducing ammonia as well as oxidizing of nitrite. Bacteria strains were obtained from the soil around dairy farm industry and observation of the potential of these isolates in reducing ammonia and oxidizing nitrite were performed. This research was first conducted by isolation of bacteria which has ability in reducing ammonia and oxidizing nitrite. Bacterial growth at solid agar medium with or without the addition of 500 mgL-1 NH4Cl was observed by measuring the colony diameter of isolates. Growth behavior in liquid medium was investigated by measuring optical density, and reduction of ammonia by isolated strains was measured by Nestler method. Results shown that 9 bacteria which able to reduce ammonia were successfully isolated from soil sample, and 5 bacteria were isolated and observe able in oxidizing nitrite. Strain TD5 which isolated from soil around the UPTD dairy farm Kaliurang and Strain PS2 isolated from UPP Pingiksari were selected as potential strains based on better growth in ammonia liquid and solid medium, and have ability to reduce ammonia concentration. The bacterial colony diameter of TD5 were 0,2 mm (with NH4Cl) and 0.19 mm (without NH4Cl) and the PS2 isolate were 0,19 mm (with NH4Cl) and 0,17 mm (without NH4Cl). The average of ammonia reduction of TD5 was 3.2 mgL-1 and PS2 was 2.9 mgL-1. Strain N3 observed having ability to increase concentration of nitrate isolated from soil around the farm calf of UPTD Kaliurang with average nitrate levels of 0.86 mgL-1.